Improving textural properties of magnesium-based metal-organic framework for gas adsorption by carbon doping - Kamal, K. (Elsevier B.V., 2021)
A magnesium-based metal-organic framework (MOF), Mg-MOF-74, has been denoted as a landmark for CO2 capture due to its highly porous structure and strong metal adsorptive sites. However, the gas uptake would be improved if particle texture could favor diffusion into the micropores and accessibility to the adsorption sites. For that reason, multi-wall carbon nanotubes (CNT) or monolayer graphene oxide (GO) was introduced into the MOF material at 0.3 wt via in-situ synthesis method as an attempt to improve gas adsorption capacities. Mg-MOF-74, Mg-MOF-74@CNT and Mg-MOF-74@GO were synthesized under solvothermal reaction and characterized by PXRD, FTIR, FESEM, TGA and N2@77 K and CO2@298 K adsorption/desorption analysis. The morphology of the Mg-MOF-74 composites showed that the particles were composed of agglomerated crystallites of which the crystal structure was well-preserved with the adjunction of carbon doping agents. The BET specific surface area and the micropore volume of the Mg-MOF-74 pristine material respectively attained 1370 m2/g and 0,4 cm3/g whilst these values were increased up to 1660â1720 m2/g and Ì´ 0.49 cm3/g for carbon composites. These variations were attributed to better activation of carbon-MOF composites thanks to more regular arrangement of the crystallites composing the agglomerates, facilitating the evaporation of the organic solvent during the thermal treatment applied in the last stage of the synthesis. The introduction of a small fraction of CNT and GO in the reactant mixture also improves the crystallization process, leading to average larger particle sizes. Consequently, the uptake of CO2 at 1 bar and 25 Â°C was shown to be improved by 18 mol and 23 mol for Mg-MOF-74@CNT and Mg-MOF-74@GO, respectively, compared with the pristine Mg-MOF-74. This current work demonstrates that by doping Mg-MOF-74 synthesis with carbonaceous agents, although at very low concentration levels, both morphological and textural properties are modified leading to larger gas adsorption capacities. Â© 2021 Elsevier Inc.